2016
DOI: 10.1093/carcin/bgw024
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism inlnc-LAMC2-1:1confers risk of colorectal cancer by affecting miRNA binding

Abstract: Genome-wide association studies (GWASs) have identified multiple susceptibility loci of colorectal cancer (CRC), however, causative polymorphisms have not been fully elucidated. Long non-coding RNAs (lncRNAs) are a recently discovered class of non-protein coding RNAs that involved in a wide variety of biological processes. We hypothesized that single nucleotide polymorphisms (SNPs) in lncRNA may associate with the CRC risk by influencing lncRNA functions. To evaluate the effects of SNPs on CRC susceptibility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 54 publications
0
64
0
1
Order By: Relevance
“…Another limitation is that we did not investigate how TXL downregulated miR-128-3p. Further research will be needed to elucidate whether TXL decreases miR-128-3p levels by directly inhibiting the transcription of its gene or, instead, acts in an indirect manner, such as by facilitating expression of endogenous RNAs (e.g., lnc-LAMC2-1:1 Gong et al, 2016) that compete with miR-128-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that we did not investigate how TXL downregulated miR-128-3p. Further research will be needed to elucidate whether TXL decreases miR-128-3p levels by directly inhibiting the transcription of its gene or, instead, acts in an indirect manner, such as by facilitating expression of endogenous RNAs (e.g., lnc-LAMC2-1:1 Gong et al, 2016) that compete with miR-128-3p.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is a complex disease that is strongly influenced by numerous mechanisms including lifestyle management, gut microbial and metabolic factors (29). Besides, with the advances of recent genome-wide association studies (GWAS) and post-GWAS studies, genetic susceptibility is also established as important roles in the development of NAFLD (30)(31)(32)(33). Though evidence from previously experimental and epidemiologic studies reported links between short sleep duration and diabetes, obesity, and metabolic syndrome, conditions that are associated with increased NAFLD risk (11,34,35), we failed to provide evidence of short sleep duration with NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that SNPs located in the binding sites of miRNAs (miRSNPs) may cause a reduction or increase in the translation of the target mRNA by affecting the binding of a miRNA to its target genes, thus altering the susceptibility to disease [22,23]. Researchers have found that the rs2910164 polymorphism in the miR-146a precursor sequence may influence the susceptibility of the Chinese population to gastric cancer, while the SNPs rs4143815 and rs4819388 in the 3'UTRs of B7-H1 and B7-H2 genes are significantly related to the occurrence of gastric cancer [24,25].…”
Section: Discussionmentioning
confidence: 99%